Determination of Genetic Variation Between Populations of Abies nordmanniana subsp. bornmulleriana Mattf According to Some Seed Characteristics - Sevik, Hakan; Yahyaoglu, Zeki; Turna, Ibrahim (InTech, 2012)
The success of any sustainable reforestation program, among other things, hinges on a continuous supply of high quality seeds for the production of the desired quantity of seedlings in nurseries or for successful stand establishment by direct sowing out in the field. What is seed quality then? Seed quality is defined as “a measure of characters or attributes that will determine the performance of seeds when sown or stored” (Hampton 2002). It is a multiple concept encompassing the physical, physiological, genetic, pathological and entomological attributes that affect seed lot performance (Basu, 1995).
Keywords: 15. Life on land